2020
DOI: 10.1021/acsabm.0c00661
|View full text |Cite
|
Sign up to set email alerts
|

Lignin in Bio-Based Liquid Crystalline Network Material with Potential for Direct Ink Writing

Abstract: The flow-induced supramolecular arrangement, or band texture, present in water-soluble anisotropic films prepared from blend solutions of hydroxypropyl cellulose and organosolv lignin is locked via esterification with bio-based polycarboxylic acids. Subsequent to shear casting of the blend solutions, the chemical cross-linking with citric acid-based cross-linkers and a dimerized fatty acid yields water-insoluble, anisotropic films prone to swelling in water. The liquid crystalline networks are analyzed by mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 69 publications
1
19
2
Order By: Relevance
“…Such a gelation time allowed for the cumulative build-up of printed layers with good control of the structure and inter-filament integration, as exemplified in Figure 1b,c, although it did not allow for overhanging structures. While the rheological properties could be tuned to allow overhanging structures by including modifiers, [28,29,32] significant changes to the ink's rheological properties could affect the ability to retain the structural color after printing. In addition, a more focused UV source might allow even faster crosslinking and consequently, reduced flow prior to gelation; however, this could compromise the integration between subsequently printed filaments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a gelation time allowed for the cumulative build-up of printed layers with good control of the structure and inter-filament integration, as exemplified in Figure 1b,c, although it did not allow for overhanging structures. While the rheological properties could be tuned to allow overhanging structures by including modifiers, [28,29,32] significant changes to the ink's rheological properties could affect the ability to retain the structural color after printing. In addition, a more focused UV source might allow even faster crosslinking and consequently, reduced flow prior to gelation; however, this could compromise the integration between subsequently printed filaments.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in this study we applied a direct ink writing approach to the HPC mesophase to introduce a larger degree of geometric flexibility. Notably, while this approach has been previously used for HPC-based composite inks, [28,29] there have not been any studies that reported cholesteric ordering in the final object. Combined with the lyotropic properties of HPC, this allows for photonic structures to be designed with independent tunability over shape and color.…”
Section: Introductionmentioning
confidence: 99%
“…Blending the lyotropic gel‐forming hydroxypropyl cellulose (HPC) with up to 25 wt % beech organosolv lignin (OSL) in an acetic acid aqueous solution delivered liquid crystalline shear thinning inks, which could be successfully direct ink written. [ 51 ] Thermal postcuring of ink formulations with polycarboxylic acid crosslinkers such as citric acid and a dimerized fatty acid, endowed parts with water insolubility and anisotropic swelling. While both HPC and lignin alone were found not to be amenable to DIW, blending these two bio‐based polymers bestowed the ink with both the required shear thinning for extrusion by virtue of the HPC liquid crystalline formation, and the needed shape retention at rest by virtue of lignin stabilizing effect.…”
Section: Diw Of Lignin Systemsmentioning
confidence: 99%
“…However, dragging of the outer layers to the center during printing limited dimensional stability and restricted the design space to continuously‐printed structures such as rings. [ 51 ] In the aim to improve solidification, shape freedom and shape retention, ethanol was further used as cosolvent of the aqueous acetic acid solution for this lignin/HPC system. [ 54 ] Prescreening of ink formulations according to Paxton et al .…”
Section: Diw Of Lignin Systemsmentioning
confidence: 99%
“…Zhang and co-workers printed colloidal lignin particles with CNFs. 49 Gleuwitz et al 50 printed blends of organosolv lignin and lyotropic hydroxypropyl cellulose. While the former study utilized minor amounts of colloidal lignin (<0.5%), Gleuwitz et al 50 could print inks with a lignin content as high as 25%.…”
Section: Introductionmentioning
confidence: 99%